3 - Transforming Labour Reserves in South Africa: Asymmetries in the New Agrarian Policy - Gilingwe Mayende (African Sociological Review, 2011)
This paper provides an analysis of the draft comprehensive rural Development Programmeof the South African government. it focuses on agrarian transformation, a component of the programme. it asks whether the potential exists within communal areas that can be tapped into to unlock and be translated into tangible benefits for the relatively large populations in such areas. Such a question is necessary, it is argued, to allow for an analysis of the agrarian structural fissures and cleavages emanating from colonialism and apartheid.